Trichoderma spp. associated with coffee in Africa: taxonomy and potential uses for the biological control of coffee leaf rust and plant growth promotion - Herrera Rodriguez, María del Carmen (2019)
Coffee leaf rust (CLR) caused by the fungus Hemileia vastatrix is the most important disease in coffee. Difficulties in obtaining long lasting resistance, the failure of the strategy of escaping the disease by highland coffee cultivation and the increasing restrictions to the use of fungicides prompted the search for alternative forms of management. Biological control is an alternative of major strategical importance in such a scenario. Although there are publications dealing with biological control of H. vastatrix, none of these studies involved fungi of the genus Trichoderma or the classical approach of biological control involving antagonists to H. vastatrix from its native range in Africa. The present work concentrated in the study of endophytic and mycoparasite Trichoderma – collected in Africa and obtained from coffee plants in wild or semi-wild conditions. Taxonomy of 94 isolates which were obtained, screening for potential antagonists to H. vastatrix and a preliminary evaluation of beneficial physiological effects of one selected isolate were performed. Among the isolates of Trichoderma obtained from Ethiopia, Cameroon and Kenya 16 distinct species Trichoderma were recognized. Twelve were known to science, namely: Trichoderma agressivum, T. andinense, T. atroviride, T. guizhouense, T. hamatum, T. koningiopsis, T. lentiforme, T. parareesei T. petersenii, T. spirale, T. theobromicola and T. virens. Four were described as new taxa: Trichoderma sp. nov.1, Trichoderma sp. nov.2, Trichoderma sp. nov.3 and Trichoderma sp. nov.4. All sporulating isolates were tested for their ability to reduce the germination of H. vastatrix urediniospores in vitro and of reducing CLR severity on leaf disc and plants. Additionally, to Trichoderma spp. some other taxa obtained as endophytes of coffee in Africa were also included in the screening. The ability of Trichoderma spp. to colonize coffee plants as endophytes after inoculation under controlled conditions was also investigated. Seventeen isolates of Trichoderma inhibited the germination of H. vastatrix urenidospores. Isolates COAD 2396 (T. atroviride), E48 (Cordyceps sp.) and E486 (Aspergillus sp.) reduced the severity of the disease to less than 50% of the levels observed in the controls when applied at 72h, 24h before or simultaneously with H. vastatrix on coffee leaf discs. Over 60% reduction of disease severity was obtained when E48 (Cordyceps sp.) was applied xiiion coffee plants 72h before inoculation with H. vastatrix. All species of Trichoderma were able to colonize coffee stems and leaves as endophytes except for COAD 2399 – Trichoderma sp. nov1. Additionally, to those studies one selected isolate (COAD 2482 - T. parareesei) was tested for growth stimulation in a model-plant species (tomato). This involved four tomato cultivars: Cereja, Italiano, Maça and Santa Cruz. The results showed that the application of the COAD 2482 isolate produced a beneficial effect which was only statistically significant for the cultivar "Santa Cruz". For that cultivar the significant effect was on the growth and development of the root system.